Effect of silicon and oxygen dopants on the stability of hydrogenated amorphous carbon under harsh environmental conditions. (April 2018) - Mangolini, Filippo; Krick, Brandon A.; Jacobs, Tevis D.B.; Khanal, Subarna R.; Streller, Frank; McClimon, J. Brandon; Hilbert, James; Prasad, Somuri V.; Scharf, Thomas W.; Ohlhausen, James A.; Lukes, Jennifer R.; Sawyer, W. Gregory; et al.
Abstract: Harsh environments pose materials durability challenges across the automotive, aerospace, and manufacturing sectors, and beyond. While amorphous carbon materials have been used as coatings in many environmentally-demanding applications owing to their unique mechanical, electrical, and optical properties, their limited thermal stability and high reactivity in oxidizing environments have impeded their use in many technologies. Silicon- and oxygen-containing hydrogenated amorphous carbon (a-C:H:Si:O) films are promising for several applications because of their higher thermal stability and lower residual stress compared to hydrogenated amorphous carbon (a-C:H). However, an understanding of their superior thermo-oxidative stability compared to a-C:H is lacking, as it has been inhibited by the intrinsic challenge of characterizing an amorphous, multi-component material. Here, we show that introducing silicon and oxygen in a-C:H slightly enhances the thermal stability in vacuum, but tremendously increases the thermo-oxidative stability and the resistance to degradation upon exposure to the harsh conditions of low Earth orbit (LEO). The latter is demonstrated by having mounted samples of a-C:H:Si:O on the exterior of the International Space Station via the Materials International Space Station (MISSE) mission 7b. Exposing lightly-doped a-C:H:Si:O to elevated temperatures under aerobic conditions or to LEO causes carbon volatilization in the near-surface region, producing a silica surface layer that protects the underlying carbon from further removal. These findings provide a novel physically-based understanding of the superior stability of a-C:H:Si:O in harsh environments compared to a-C:H. Graphical abstract: A silicon- and oxygen-containing hydrogenated amorphous carbon (a-C:H:Si:O) coating was exposed to the harsh conditions of the low Earth orbit (LEO) environment (hyperthermal atomic oxygen, thermal cycling, ultraviolet radiation) aboard the International Space Station. X-ray photoelectron spectroscopy measurements indicated degradation of the near-surface region of a-C:H:Si:O through breakage and subsequent oxidation of carbon-carbon bonds as well as formation of a silica layer (shift of the silicon 2p signal to higher binding energies). Image 1